Population genetic structure and dispersal in white-lipped peccaries (Tayassu pecari) from the Brazilian Pantanal - Biondo, Cibele [UNESP]; Keuroghlian, Alexine; Gongora, Jaime; Miyaki, Cristina Y. (Alliance Communications Group Division Allen Press, 2011)
In many mammals social organization promotes genetic structuring, which can be influenced by the dispersal pattern of the species. We analyzed the population genetic structure and dispersal of white-lipped peccaries (Tayassu pecan) from the Pantanal, Brazil. We genotyped 100 individuals at 7 microsatellite loci from 2 adjacent locations with no obvious geographic barrier between them. We found a significant but low F(ST) value, and the Bayesian analysis indicated a unique cluster. No significant differences were observed between mean assignment indices of resident males and females from both locations, and the probability of being born at the location sampled of > 30% of the individuals analyzed was lower than average. Mean relatedness between resident female, male, and opposite-sex pairs was not statistically different in both locations. These results suggest a low degree of genetic differentiation between the locations analyzed, and dispersal by both sexes (contrary to the predicted male-biased dispersal of most mammalian species).
Keywords: Bayesian approach; dispersal; microsatellite markers; Pantanal wetland; Tayassu pecari; Tayassuidae